Alternative pathways to legitimacy: promotional practices in the Ontario for-profit college sector. Issue 1 (2nd January 2017) - Pizarro Milian, Roger; Quirke, Linda
ABSTRACT: This study empirically examines how for-profit career colleges in Ontario, Canada market themselves to prospective students. It uses a mixed-methods approach to review the content of 489 online promotional profiles representing 375 unique for-profit colleges. It finds that for-profit colleges adopt several distinct marketing strategies, including (1) emphasizing their expedient provision of modern, practical skills and (2) the convenience afforded by the location of their campuses. We interpret these findings through the lens of the new institutionalist theoretical perspective, highlighting how these organizations draw upon alternative strategies to legitimate their chosen forms.